Data from: When Bergmann's rule fails: evidences of environmental selection pressures shaping phenotypic diversification in a widespread seabird - Nunes, Guilherme Tavares; Mancini, Patrícia Luciano; Bugoni, Leandro (2020)
Organisms tend to exhibit phenotypes that can be shaped by climate, commonly demonstrating clinal variations along latitudinal gradients. In vertebrates, air temperature plays a major role in shaping body size in both ectothermic and endothermic animals. However, additional small-scale environmental factors can also act as selection pressures in the marine ecosystem (e.g. primary productivity), evidencing multi-scale processes acting on marine organisms. In this study, we tested Bergmann's rule in a widely distributed seabird, the brown booby Sula leucogaster, in addition to evaluating the relationship of sea surface temperature and chlorophyll α with phenotypes. We used traits from a morphometric dataset (culmen, wing chord, and tarsus length) and body mass of 276 brown boobies distributed on six breeding sites along a latitudinal gradient in the South Atlantic Ocean (0–27°S). We found significant differentiation among colonies, but phenotypic similarities were observed between colonies located at the extremes of the latitudinal gradient. As the colony nearest to the Equator, Saint Peter and Saint Paul archipelago, had the largest and heaviest individuals, the model containing only air temperature explained < 5% of the allometric variation, providing no substantial support for Bergmann's rule. However, when we added the interaction of chlorophyll α and sea surface temperature the deviance explained rose to over 80%. Primary productivity and sea surface temperature do not follow a latitudinal gradient in the ocean and, therefore, the role of small-scale oceanographic processes in shaping body size and the importance of considering additional environmental variables when testing Bergmann's rule in marine organisms are evident. Dryad_ECOG_E02209_Nunes et al._2016Phenotypic data of brown boobies from six colonies along the South Atlantic Ocean; plus latitude, air temperature, and sea surface temperature data.Dryad_ECOG_E02209.xlsx